An Intracellular Laccase Is Responsible for Epicatechin-Mediated Anthocyanin Degradation in Litchi Fruit Pericarp. Issue 4 (29th October 2015) - Fang, Fang; Zhang, Xue-lian; Luo, Hong-hui; Zhou, Jia-jian; Gong, Yi-hui; Li, Wen-jun; Shi, Zhao-wan; He, Quan; Wu, Qing; Li, Lu; Jiang, Lin-lin; Cai, Zhi-gao; et al.
Abstract : Anthocyanin degradation by an intracellular laccase, mediated by epicatechin oxidation, causes the loss of red color in Lichi fruit peel. Abstract: In contrast to the detailed molecular knowledge available on anthocyanin synthesis, little is known about its catabolism in plants. Litchi ( Litchi chinensis ) fruit lose their attractive red color soon after harvest. The mechanism leading to quick degradation of anthocyanins in the pericarp is not well understood. An anthocyanin degradation enzyme (ADE) was purified to homogeneity by sequential column chromatography, using partially purified anthocyanins from litchi pericarp as a substrate. The purified ADE, of 116 kD by urea SDS-PAGE, was identified as a laccase (ADE/LAC). The full-length complementary DNA encoding ADE/LAC was obtained, and a polyclonal antibody raised against a deduced peptide of the gene recognized the ADE protein. The anthocyanin degradation function of the gene was confirmed by its transient expression in tobacco ( Nicotiana benthamiana ) leaves. The highest ADE/LAC transcript abundance was in the pericarp in comparison with other tissues, and was about 1, 000-fold higher than the polyphenol oxidase gene in the pericarp. Epicatechin was found to be the favorable substrate for the ADE/LAC. The dependence of anthocyanin degradation by the enzyme on the presence of epicatechin suggests an ADE/LAC epicatechin-coupled oxidation model. This model was supported by a dramatic decrease in epicatechin content in the pericarp parallel to anthocyanin degradation. Immunogold labeling transmission electron microscopy suggested that ADE/LAC is located mainly in the vacuole, with essential phenolic substances. ADE/LAC vacuolar localization, high expression levels in the pericarp, and high epicatechin-dependent anthocyanin degradation support its central role in pigment breakdown during pericarp browning.